2004
DOI: 10.1055/s-2004-822825
|View full text |Cite
|
Sign up to set email alerts
|

Antibakterieller Effekt hochenergetischer extrakorporaler Stoßwellen: Ein in vitro Nachweis

Abstract: ESWT proved to exert a significant antibacterial effect on clinically relevant pathogens. Further investigations on energy flux density and impulse rates might contribute to an optimization of the bactericidal effectiveness. Infections as possible indications of the ESWT should therefore be assessed in further studies and the clinical relevance should be verified in an animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Finally, according to our findings, we suggest that combinations of biofilm-validated antibiotics with shock wave therapy should be further investigated against C. acnes biofilms, as recent in vitro studies have suggested that such treatment combinations are highly effective against biofilms produced by clinically relevant aerobic bacteria [12,52,53].…”
Section: Study Limitations and Implications For Future Researchsupporting
confidence: 66%
See 1 more Smart Citation
“…Finally, according to our findings, we suggest that combinations of biofilm-validated antibiotics with shock wave therapy should be further investigated against C. acnes biofilms, as recent in vitro studies have suggested that such treatment combinations are highly effective against biofilms produced by clinically relevant aerobic bacteria [12,52,53].…”
Section: Study Limitations and Implications For Future Researchsupporting
confidence: 66%
“…Based on the results of prior in vitro laboratory studies, extracorporeal shock wave therapy (ESWT) presents a promising track record of properties against biofilms produced by clinically relevant aerobic microorganisms [11,12]. While the exact mechanism of the bactericidal action of shock waves still remains unclear [13], it has been postulated that shock wave antibacterial activity occurs at a cell wall level through an increase in permeabilization of bacterial cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, on-demand activation could be an additional modality in addressing implant-related infections. Previous studies have demonstrated a reduction in biofilm presence both in vitro and in vivo when exposed to shock wave treatment [ 39 , 40 , 41 , 42 , 43 ]. The concrete effects of the shock waves have not yet been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“… susp Johannes et al 1994 [ 10 ] em cgel,mem,water tube PP susp Oosterhof et al 1989 [ 41 ] em cgel,mem,water tube PE susp Kusnierczak et al 2000 [ 16 ] em cgel,mem,water tube ? adh Gollwitzer et al 2004 [ 52 ] em cgel,mem,water pipette PE susp Suhr et al 2013 [ 73 ] em cgel,mem,med plate/dish ? adh SW shockwave technology, eh electrohydraulic, em electromagnetic, p piezoelectric, cgel coupling gel, mem membrane, med cell culture medium, custom custom made, PP polypropylene, PE polyethylene, PS polystyrene, PVC polyvinyl chloride, susp suspension, adh adherent, pel pellet/sediment, gel embedded in gel, organ organ or tissue sample The material of the cell container because the sound field inside it can be modified by reflection, diffraction, refraction, and absorption.…”
Section: Methodsmentioning
confidence: 99%